Pengaruh Pengaruh dewan komisaris independen, kepemilikan manajerial dan kepemlikan institusional terhadap profitabilitas - Khotimah, Miftahul; Huda, Syamsul (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This This study aims to analyze the effect of independent commissioners, managerial ownership, and institutional ownership on profitability in textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Profitability is measured using Return on Assets (ROA). The research employs a quantitative method with a descriptive and verificative approach. The sample was determined using purposive sampling, resulting in 9 companies with a total of 45 data samples. The data analysis technique used is multiple linear regression. The results of the study show that the significance obtained is 0.021 < 0.05 with a t-table value (36-3 = 33) of 2.03452, and the calculated t-value > t-table (2.430 > 2.03452), which means that (1) partially, independent commissioners have a significant positive effect on profitability. A significance value of 0.021 < 0.05 with a t-table (36-3 = 33) of 2.03452 and a calculated t-value > t-table (2.423 > 2.03452) indicates that (2) managerial ownership has a significant negative effect on profitability. Furthermore, a significant value of 0.010 < 0.05 with a t-table (36-3 = 33) of 2.03452 and a calculated t-value > t-table (2.737 > 2.03452) indicates that (3) institutional ownership also has a significant negative effect on profitability. (4) Simultaneously, the f-table value (36-3 = 33) is 2.89, while the obtained f-value is 3.969 > 2.89 with a significance of 0.016 < 0.05, which means that independent commissioners, managerial ownership, and institutional ownership together have a significant effect on the profitability of textile and garment sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Keywords: independent commissioners, managerial ownership, institutional ownership, profitability